If lo g a x = 3 and lo g b x = 4 , then lo g a b x = ? Express your answer as a decimal rounded to three decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I'm well satisfied with such an explanation
We are given that lo g a x = 3 and that lo g b x = 4 . Our objective is to find what lo g a b equals to. Well, to do this, we must first rewrite the given logarithms using a different form. This gives us that lo g a x = 3 ⟹ lo g ( a ) lo g ( x ) = 3 and that lo g b x = 4 ⟹ lo g ( b ) lo g ( x ) = 4 . We can see that both logarithmic function have lo g ( x ) as their numerators, which will be used later. Now, we can move on to finding what lo g a b x is. Since lo g a b is the same thing as lo g a + l o g b , we can create the following expression: lo g a b lo g ( x ) ⇒ lo g a + lo g b lo g ( x ) . Now is the part where it gets somewhat tricky. We can use another rule for logarithms to get the following derived expressions for lo g a x = 3 and lo g b x = 4 - 3 lo g ( x ) + 4 lo g ( x ) lo g ( x ) ⟹ 3 1 + 4 1 1 ⇒ 1 2 7 1 ⇒ 7 1 2 ≈ 1 . 7 1 4
@Vishruth Bharath , just like \frac 12 2 1 , \sin \theta sin θ , \tan tan and \ln ln , you need to put a backslash before log. See the different log x l o g x and \log x lo g x . Note that the function simbol log is not in italic which is for variable and constant. Note that x is in italic. Also note that a space is provided between log and x for the one with backslash while the one without has no space.
Log in to reply
Oh, I didn't know that. Thanks!
Thanks so much for the advice!
By the properties of logarithms, lo g x a = 3 1 and lo g x b = 4 1 . Thus,
lo g a b x = lo g x a b 1 = lo g x a + lo g x b 1 = 3 1 + 4 1 1 = 7 1 2 ≈ 1 . 7 1 4 .
lo g a x = 3 ⟹ a 3 = x , lo g b x = 3 ⟹ b 3 = x , and lo g a b x = y ⟹ ( a b ) y = x .
If x = a 3 = b 4 , then a = b 3 4 .
If a = b 3 4 and x = b 4 , then ( a b ) y = x ⟹ ( b 3 4 b ) y = b 4 ⟹ b 3 7 y = b 4 ⟹ 3 7 y = 4 ⟹ y = 7 1 2 ≈ 1 . 7 1 4 .
Problem Loading...
Note Loading...
Set Loading...
From lo g b x = 4 , ⟹ lo g a b lo g a x = lo g a b 3 = 4 , ⟹ lo g a b = 4 3 . Then we have lo g a b x = lo g a ( a b ) lo g a x = lo g a a + lo g a b 3 = 1 + 4 3 3 = 7 1 2 ≈ 1 . 7 1 4